Biliary excretion in persons with low blood glutathione levels - Ankrah, N.; Dunyo, S.K.; Nyarko, A.K.; Appiah-Opong, R.; Ofosuhene, M. (East African Medical Journal, 1998)
A study to investigate the association between blood glutathione (GSH) levels and biliary excretory status was conducted in apparently healthy Ghanaian subjects without frank biliary disease and anaemia. The results showed that, in adults (mean age: 38.5 years) and children (mean age: 13.0 years), plasma conjugated bilirubin is inversely correlated with blood GS (respective site r=-0.524, p<0.011 and -0.395, p<0.005). Persons with elevated plasma conjugated bilirubin compared to controls (mean: 6.0 versus 2.5 umol/L, p<0.001) also exhibited low blood GSH values (3.5 versus 4.2 umol/gHb, p<0.029). Malaria parasites with counts up to 2,453 parasites/ul blood had no effect on the obtained data. The results suggest that low blood GSH levels may be relevant to delays in biliary excretion of conjugated toxins from the liver, as exemplified by the rise in conjugated bilirubin levels in the plasma, and predispose liver cells to increased oxidant state and damage.
Keywords: Lithiasis; Gallbladder; Pathogenesis; Glutathione; Blood; Low; Assay; Human; Ghana; Africa; Biliary tract disease; Digestive diseases